Barriers and facilitators of physical activity in children with bronchiectasis: Perspectives from children and parents - Jones, Taryn; Baque, Emmah; O’Grady, Kerry-Ann F.; Goyal, Vikas; Chang, Anne B.; Trost, Stewart G. (Frontiers in Pediatrics, 2022)
Background: Current bronchiectasis management guidelines recommend regular physical activity but a large proportion of children with bronchiectasis do not meet public health recommendations which call for 60 min or more of moderate-to-vigorous intensity physical activity daily. Knowing the factors that influence physical activity in children with bronchiectasis is necessary for the development of effective interventions to increase physical activity in this patient group. The objective of this study was to identify facilitators and barriers to physical activity in children with bronchiectasis unrelated to cystic fibrosis (CF) from the perspectives of children and their parents. Methods: This was a qualitative study informed by the Theoretical Domains Framework (TDF). Children aged 7 to 15 years (8.8 y, 8.4-11.0) (median, interquartile range) and parents (45.8 y, 39.7 – 48.3) completed separate, semi-structured interviews (n = 21). Recordings were transcribed verbatim, and barriers and facilitators related to each TDF domain deductively coded. Emergent themes were inductively derived via consensus moderation. Results: From the perspectives of children, fun with friends, organized sport and activities, and family co-participation in physical activity emerged as facilitators. Inability to keep up with their peers and time on technology emerged as barriers. From the perspectives of parents, instrumental and logistic support for physical activity and supportive social and physical activity environments emerged as facilitators, while management of symptoms associated with bronchiectasis emerged as a barrier. Conclusion: Programs to increase physical activity in children with bronchiectasis should be fun, accessible, provide opportunities for social interaction and address barriers related to exercise tolerance, perceived competence, and presence of respiratory symptoms.